Psychometric properties of the Children's Eating Behavior Questionnaire in Mexican children under 3 years of age - Cárdenas-Villarreal, Velia Margarita; Cynthia Berenice , Cynthia Berenice; Hernández- Martínez , Nora; Cruz-Chávez, Norma Edith; Guevara-Valtier , Milton Carlos (Horizonte Sanitario, 2022)
Objective: Mexico is one of the countries with the highest prevalence ofchildhood obesity worldwide. Valid comprehensive assessment instrumentsare required to address the problem. The Child Eating Behavior Questionnaire(CEBQ) allows the assessment of children's eating behaviors related to obesityrisk, so the following objective was to evaluate the psychometric properties ofthe original version of the CEBQ in Mexican children aged 1 to 3 years.Material and Methods: 201 mothers residing in northeastern Mexicocompleted the CEBQ in community health centers. A confirmatory factoranalysis (CFA) was performed through principal components and reliability(internal consistency) with Cronbach's alpha (α).Results: A model with seven factors and 24 items was identified, the goodnessof-fit indices of the proposed model were adequate: comparative fit index (CFI=0.90), and root mean square error of approximation (RMSEA= 0.06). The factorsthat make up the CEBQ have acceptable internal reliability α > 0.70.Conclusion: The CEBQ in Mexican children aged 1 to 3 years has psychometricproperties that make it a reliable and valid measure to assess eating behaviorsrelated to obesity risk. It is recommended to contrast this model in similarpopulations.Keywords: Childhood obesity; feeding behavior; Infant; Child, Preschool